A victim of regulatory arbitrage? Automatic exchange of information and the use of golden visas and corporate shells. Issue 3 (16th October 2020) - Ahrens, Leo; Hakelberg, Lukas; Rixen, Thomas
Abstract: The multilateral adoption of the automatic exchange of information (AEI) on bank accounts held by nonresidents was a breakthrough in the fight against cross‐border tax evasion, which led to a substantial reduction in the value of bank deposits and investment portfolios in traditional tax havens. However, there is suspicion that sophisticated tax evaders engage in regulatory arbitrage of AEI provisions. We examine whether two widely discussed secrecy schemes, namely golden visas and anonymous trusts and shell corporations, have been used to circumvent information reporting. Relying on a difference‐in‐difference design, we only find scattered evidence for use of the secrecy schemes. Overall, our results suggest that regulatory arbitrage is not yet widespread, but it seems to increase over time. We thus provide evidence for the current effectiveness of the AEI but also show that closing remaining loopholes is of utmost importance. We link our findings to debates about the (im)possibility of re‐embedding neoliberal globalization.